2010
DOI: 10.1371/journal.pone.0008670
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Localization of Vitamin D Receptor in Human Platelets and Differentiated Megakaryocytes

Abstract: BackgroundLike other steroid hormones, vitamin D elicits both transcriptional events and rapid non genomic effects. Vitamin D receptor (VDR) localization and mechanisms of VDR-triggered non genomic responses are still controversial. Although anticoagulant effects of vitamin D have been reported and VDR signalling has been characterized in monocytes and vascular cells, nothing is known about VDR expression and functions in human platelets, anucleated fragments of megakaryocytes which are known targets of other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(108 citation statements)
references
References 48 publications
2
103
0
3
Order By: Relevance
“…In this context, we show that mitochondrial injury linked to AT 1 /VDR uncoupling was improved when paricalcitol, enalapril, or, better still, the combination of both was used. This finding is feasible taking into consideration recent contributions that reported the identification and characterization of a functional mitochondrial RAS (Abadir et al 2011), the mitochondrial localization of VDR (GarcĂ­a et al 2012 andSilvagno et al 2010), and ultrastructural mitochondrial improvement as a consequence of recovery in mitochondrial VDR expression linked to poor AT 1 and NADPH oxidase activity during obstructive nephropathy. Moreover, a ligand-independent mitochondrial import of VDR through the permeability transition pore (PTP) was reported (Silvagno et al 2013); and since functional and structural changes in mitochondria are caused by the opening of the mitochondrial PTP and by the mitochondrial generation of ROS, this finding open new perspectives on PTP function as transporter and on VDR role in mitochondria.…”
Section: Discussionmentioning
confidence: 73%
“…In this context, we show that mitochondrial injury linked to AT 1 /VDR uncoupling was improved when paricalcitol, enalapril, or, better still, the combination of both was used. This finding is feasible taking into consideration recent contributions that reported the identification and characterization of a functional mitochondrial RAS (Abadir et al 2011), the mitochondrial localization of VDR (GarcĂ­a et al 2012 andSilvagno et al 2010), and ultrastructural mitochondrial improvement as a consequence of recovery in mitochondrial VDR expression linked to poor AT 1 and NADPH oxidase activity during obstructive nephropathy. Moreover, a ligand-independent mitochondrial import of VDR through the permeability transition pore (PTP) was reported (Silvagno et al 2013); and since functional and structural changes in mitochondria are caused by the opening of the mitochondrial PTP and by the mitochondrial generation of ROS, this finding open new perspectives on PTP function as transporter and on VDR role in mitochondria.…”
Section: Discussionmentioning
confidence: 73%
“…20 VDRs have been found in all the major cardiovascular cell types, including VSMC, 21 EC, 22 cardiomyocytes, 23 most immune cells, 24 and platelets. 25 VDR binds 1,25(OH) 2 D with high affinity and specificity and then heterodimerizes predominantly with retinoid X receptor ( Figure 2). Structurally, VDR consists of a short N-terminal domain before the DNA-binding domain comprising 2 zinc fingers, the first conferring vitamin D response element specificity and the second providing a site for heterodimerization.…”
Section: Vitamin D Receptormentioning
confidence: 99%
“…Some of the most interesting advances in VitD signalling are the recent studies demonstrating VDR translocation to the mitochondria (mito-VDR) in various cell types and the subsequent direct impact on cell metabolism (Silvagno et al 2010, Consiglio et al 2014. These interactions may have important implications for the rapid non-genomic responses observed previously, like the insulinotropic actions in pancreatic ÎČ-cells (Kajikawa et al 1999) and are unlike those observed for nuclear or membrane VDR.…”
Section: Perspectives For Future Studiesmentioning
confidence: 99%